Leadership as lunacy and other metaphors for educational leadership - Lumby, Jacky
This title provides an innovative look at leadership models and behaviours and what school leaders and stakeholders alike can learn from them. The authors guide readers on a journey of 'intellectual pyrotechnics', drawing you through cognitive possibilities that inspire and provoke reflection on the state of leadership in education
Keywords: Educational leadership; Schulleitung